Complete mitochondrial genome of Cygnus cygnus (Aves, Anseriformes, Anatidae). (3rd July 2016) - Park, Chang Eon; Park, Gun-Seok; Kwak, Yunyoung; Hong, Sung-Jun; Rahim Khan, Abdur; Kwon Jung, Byung; Park, Yung-Jun; Kim, Jong-Guk; Cheon Park, Hee; Shin, Jae-Ho
Abstract: In this study, the complete mitochondrial genome of Cygnus cygnus (Aves, Anseriformes, Anatidae) was sequenced. The genome, consisting of 16 724 base pairs (bp), encoded 13 protein coding genes (PCGs), two ribosomal RNAs (rRNAs), 22 transfer RNAs (tRNAs), and a control region (CR). Two rRNA genes for 12S rRNA (991 bases) and 16S rRNA (1608 bases) are located between tRNA-Phe and tRNA-Leu (UUR) and divided by the tRNA-Val. The CR, of 1156 bp in length, is located between tRNA-Glu and tRNA-Phe. The overall base composition of C. cygnus is G + C: 47.2%, A + T: 52.8%, apparently with a slight AT bias. Phylogenetic analysis showed that the C. cygnus was closed to Cygnus columbianus .